2011
DOI: 10.1371/journal.pone.0025957
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Disease in Children in Merseyside, England: A 31 Year Descriptive Study

Abstract: Meningococcal disease (MCD) is the leading infectious cause of death in early childhood in the United Kingdom, making it a public health priority. MCD most commonly presents as meningococcal meningitis (MM), septicaemia (MS), or as a combination of the two syndromes (MM/MS). We describe the changing epidemiology and clinical presentation of MCD, and explore associations with socioeconomic status and other risk factors. A hospital-based study of children admitted to a tertiary children's centre, Alder Hey Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In a 31-year descriptive study, Stanton et al characterized the cases of meningococcal disease admitted to a tertiary children center in England and identified a significant proportion of cases caused by MenB with the majority of cases occurring below 4 years of age. In this study, the proportion of cases due to MenC increased significantly until the year 2000, when meningococcal vaccination reduced the number of cases to very low levels [16].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a 31-year descriptive study, Stanton et al characterized the cases of meningococcal disease admitted to a tertiary children center in England and identified a significant proportion of cases caused by MenB with the majority of cases occurring below 4 years of age. In this study, the proportion of cases due to MenC increased significantly until the year 2000, when meningococcal vaccination reduced the number of cases to very low levels [16].…”
Section: Discussionmentioning
confidence: 56%
“…In 2005, the quadrivalent meningococcal conjugate vaccine was licensed for use in adolescents and adults in the USA. Large scale MenC-V vaccination has drastically reduced the incidence of MenC-disease in several countries [13], [16], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Neisseria meningitidis is feared among health care personnel and lay people owing to its propensity to cause acute meningitis and fulminant septicemia, often in clusters of the population Rosenstein et al, 2001;Stephens et al, 2007). The case fatality rate of systemic meningococcal disease (SMD) has remained fairly stable around 10% since the introduction of sulfa therapy in the 1930s and penicillin in the 1940s (Barquet et al, 1999;Brooks et al, 2006;Stanton et al, 2011;Stoof et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 30 studies reported impact of MCCV vaccination programs and 17 studies reported vaccine effectiveness (direct effect) of MCCV. Studies came from 9 different countries; 11 from England and Wales/UK [20][21][22][23][24][25][26][27][28][29][30], 10 from Spain [31][32][33][34][35][36][37][38][39][40], 5 from Canada [41][42][43][44][45], 4 each from Brazil [46][47][48][49] and Italy [50][51][52][53], 2 each from Australia [54,55] and the Netherlands [56,57], and one each from Germany [58] and Belgium [59]. The MCCV were introduced as part of the routine childhood NIP in all these countries.…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 studies evaluating the impact of the program. Four out of six studies represented earlier post-MCCV periods before 2003 [20][21][22][23] and 2 studies covered later periods between 2006 and 2013 [24,25]. No studies following the 2013 schedule change were available/included in the analysis.…”
Section: United Kingdommentioning
confidence: 99%